THE EFFECT OF NUTRITION AND EXERCISE EDUCATION ON THE DEVELOPMENT OF ATTITUDE AND BELIEF OF UNIVERSITY STUDENTS TOWARDS OBESITY: CASE OF ELAZIĞ PROVINCE - Çelebi, Evrim; Kadioglu, Bircan Ulas; Uncu, Fatos (My University, 2021)
In order to determine the effect of nutrition and exercise education on the development of students' attitudes and beliefs towards obesity, this study was conducted with a control group quasi-experimental pretest-posttest design. The research was conducted in the fall semester of the 2019-2020 academic year between October-November 2019. The study group consisted of 50 female students, 25 experimental (overweight or obese) and 25 control group (normal weight), studying at Fırat University Faculty of Health Sciences. In order to collect pretest data, a personal information form and Health Belief Model Scale in Obesity (HBMSO) were applied to the students in the experimental and control groups. Later, the students in the experimental group were taken to a 6 week program with 2 hours of healthy nutrition and exercise education per week. HBMSO, which was applied to the students in the experimental and control groups at the beginning of the study, was repeated at the end of the education, thus the posttest data were collected. When the before and after education HBMSO sub-dimension scores of the experimental and control groups were compared; The difference in the attitude to importance of health, perceived sensitivity, perceived severity, perceived usefulness and perceived disability dimensions in the experimental group was found to be significant (p<0.001). HBMSO subscale scores of the control group did not show any difference (p>0.05). As a result, after nutrition and exercise education given to obese students, a positive change was achieved in students' beliefs about obesity.
Keywords: Beslenme ve Diyetetik; Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri; Spor Bilimleri